Superior Cycling Stability and Fast Reaction Kinetics of NaV2.9Mg0.1(PO4)3/C Anode for Sodium‐Ion Batteries. Issue 11 (28th August 2019) - Huang, Yunxuan; Wan, Xin; Luo, Dongxue; Tian, Guorong; Xiang, Xingde; Sun, Molong
Abstract : Developing sodium‐storage electrode materials with fast reaction kinetics and good cycling stability is of much importance for realizing applications of sodium‐ion batteries (SIBs) in the field of power devices such as electric vehicles. Herein, an NaV2.9 Mg0.1 (PO4 )3 /C nanocomposite is reported as a novel high‐performance anode material for SIBs, which is prepared by using a facile sol–gel approach. Techniques consisting of X‐ray diffraction, transmission electron microscopy, cyclic voltammetry, and galvanostatic measurements are used to analyze structural properties and electrochemical performance of the material. Due to the reversible sodium intercalation chemistry and fast reaction kinetics, the material shows excellent high‐rate capability with 148 mAh g −1 at 50 mA g −1 and 86 mAh g −1 at 2000 mA g −1, and outstanding cycling stability with 97% capacity retention after 200 cycles at 100 mA g −1 . In particular, full SIBs assembled with NaV2.9 Mg0.1 (PO4 )3 /C anode and Na3 (VO)2 (PO4 )2 F/C cathode exhibit a remarkable cycling lifetime over 1000 cycles. The finding suggests promising application of the NaV2.9 Mg0.1 (PO4 )3 /C anode for power‐type batteries. Abstract : An NaV2.9 Mg0.1 (PO4 )3 /C nanocomposite is reported as a novel anode material for high‐performance sodium‐ion batteries, showing superior cycling stability with capacity retention of 97% after 200 cycles at the current of 100 mA g −1 . Coupled with a Na3 (VO)2 (PO4 )3 /C cathode, it exhibits a practical specific energy of 173 Wh kg −1 with an impressive cycling lifetime over 1000 cycles.